'Doing family' through ICT‐mediated ordinary co‐presence: transnational communication practices of Romanian migrants in Switzerland. (8th February 2016) - NEDELCU, MIHAELA; WYSS, MALIKA
Abstract: In this article, we account for the emergence of new 'being together' practices that transnational families develop through ICT‐mediated communication. Drawing on the case of Romanian migrants in Switzerland, we show how political and technological factors, family norms and obligations, as well as individual preferences and aspirations interact and generate novel ordinary co‐presence routines that rely on multiple media affordances to recreate a space for family practices and shape different ways of 'doing family' at a distance. This study shows how a subtle sense of each other's everyday life combines with possibilities and feelings of 'being and doing things together' at a distance, through multimodal interactions, reflected in ritual, omnipresent and reinforced co‐presence routines. Although these routines are the drivers of new forms and feelings of togetherness, they generate ambivalent effects that range from immediate reciprocal wellbeing and emotional comfort to new expectations of solidarity, family tensions and constraints. In conclusion, ICT‐mediated ordinary co‐presence not only mirrors the 'normal' functioning of transnational families, but it also reflects, more generally, an expression of the cosmopolitanization of everyday life.